Influência da qualidade de vida relacionada à saúde bucal no consumo de substâncias lícitas em adolescentes: um estudo de coorte - Brondani, Bruna (2019)
The consumption of alcohol and cigarette is considered one of the biggest public health problems nowadays. Several risk factors for the consumption of these substances have been identified. However, the proportion of consumers remains high in Brazil and worldwide, especially among adolescents. It has been verified that psychosocial predictors influence the consumption of health harmful substances, since they may influence the individual's perception of their position into the society. In this way, the adoption of risk behaviors in situations of health inequities is facilitated. Therefore, it is important to evaluate the relationship between psychosocial predictors focused on the impact of oral conditions, such as Oral Health Related Quality of Life (OHRQoL), and deleterious health habits, such as alcohol and cigarette consumption. The aim of this study was to evaluate the influence of OHRQoL on the consumption of harmful substances in adolescents. This study belongs to a prospective cohort that began in 2012 with a random sample of 1134 12-year-old schoolchildren in the city of Santa Maria, RS, Brazil, who were followed up for 6 years. Data used in the present study were collected in the two cohort reassessments, which occurred in 2014 (T2) and 2018 (T3). OHRQoL was measured using the Brazilian short version of the Child Perceptions Questionnaire (CPQ 11-14) at T2. Demographic, socioeconomic and oral health measures were also collected during this period. The consumption of alcohol and cigarette was evaluated at T3 through a self-administered questionnaire. Data were analyzed using multilevel Poisson regression models to investigate the influence of predictor variables on the consumption of harmful substances among adolescents. This approach provides the incidence rate ratio (IRR) and their respective confidence intervals (CI). From the 770 adolescents followed up at T2, 561 and 562 were reevaluated for alcohol and cigarette consumption, respectively. Adolescents with higher CPQ11-14 overall score had a higher risk of regularly consuming alcohol (IRR 1.01, 95% CI 1.01-1.02) and cigarette (IRR 1.04, 95% CI 1.03-1.05). Regarding demographic and socioeconomic variables, non-white adolescents, boys, belongings to low-income families whose mothers had less than 8 years of education showed a higher consumption of alcohol and cigarettes. In addition, participants who did not visit the dentist in the last 6 months and had worse clinical conditions, such as dental caries, malocclusion and perceived gingival bleeding, also had an increased risk for the consumption of these harmful substances. Therefore, adolescents with worse OHRQoL presented a higher consumption of alcohol and cigarette. This knowledge is useful for the planning of public health policies aimed at improving the quality of life of adolescents and, consequently, reducing the consumption of harmful substances in society.